Pengembangan Aplikasi Gim Edukasi Pengenalan Buah-buahan Berbasis Android - Ahmad Syahroni Deniwinata (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop an educational game as an alternative medium in learning English based on Android, entitled "Fruit POP". The game is developed using Unity and the C# programming language. The development method used in this research is Game Development Life Cycle (GDLC) with 6 stages, namely Initiation, Pre-Production, Production, Testing, Beta, and Release stages. The game can be played offline and can be downloaded by android smartphone users. The final result of this study is the data obtained by beta testing with 52.4% results stated that respondents answered "agree" and 28,6% respondents answered “very agree” that this game can be an alternative learning media.